Histological changes in dental pulp tissue with age: a comparative study: Age-related histological changes in dental pul - H. Warwar, Abdul Nasser; I. Abdullah, Mohammed; A. Sami, Wesam; Mohammed, Waleed K. (Cellular and Molecular Biology, 2025)
The dental pulp undergoes several histological changes with age. These include a reduction in the number of cells and blood vessels, resulting in a decreased capacity for regeneration and repair. Furthermore, there is an increase in collagen fiber density and the formation of secondary dentin, which reduces the volume of the pulp chamber. This study performed a comparative histological analysis to characterize these age-related changes in dental pulp tissues. A cross-sectional comparative analysis was conducted to examine the histological changes in dental pulp tissue from two distinct age groups. Extracted teeth were thoroughly cleaned and immediately fixed in 10% formalin for preservation. Each sample was then decalcified using 10% formic acid for a duration sufficient to allow sectioning without damaging the tissue. After decalcification, the teeth were embedded in paraffin wax, and serial sections, with a thickness of 4-6 μm, were prepared using a microtome. The sections were then stained with Hematoxylin and Eosin (H&E) to visualize general tissue structure. The histological analysis demonstrated notable differences in dental pulp tissue between the two age groups. Group A (young) samples showed a high cellularity, with numerous fibroblasts and odontoblasts and a clearly defined odontoblastic layer. However, Group B (elderly) samples exhibited a marked reduction in cellularity, with fewer odontoblasts present and evidence of increased fibroblast degeneration. The histological changes observed in our study underscore the impact of aging on dental pulp tissue.